Механізми управління якістю в сфері туризму: трансфер міжнародного досвіду в українські реалії - Демко, Валентина Сергіївна; Demko, Valentina (My University, 2025)
UA: У статті здійснено комплексне дослідження механізмів управління якістю в туризмі з акцентом на транс фер провідного міжнародного досвіду в українські реалії. Обґрунтовано актуальність проблеми підвищення якості туристичних послуг в умовах глобальної конкуренції та динамічних змін ринкового середовища. Роз крито ефективні інструменти інституційного та нормативного регулювання, сертифікації, аудиту, професій ної підготовки кадрів, що забезпечують сталість і конкурентоспроможність туристичних послуг. Проаналі зовано сучасний стан системи управління якістю в туристичній сфері України. Визначено ключові бар’єри інтеграції – фрагментарність регулювання, обмежена участь суб’єктів галузі в системах добровільної сер тифікації, відсутність національної системи оцінки якості турпродукту. Ідентифіковано релевантні інстру менти, що можуть бути імплементовані в Україні з урахуванням локальних умов функціонування туристич них підприємств. У результаті дослідження запропоновано аналітичну типологію моделей забезпечення якості, адаптовану до українських реалій, та охарактеризовано їх порівняльні характеристики. /// EN: The article provides a comprehensive study of quality management mechanisms in the tourism sector, with an emphasis on transferring leading international experience to Ukrainian realities. The relevance of improving the quality of tourism services in the context of global competition and dynamic changes in the market environment is substantiated. The theoretical foundations of quality management are considered through the prism of the evolution of conceptual approaches – from classical quality control models to modern management systems based on ISO, TQM, EMAS, and GSTC standards, which are actively used in the EU, Canada, Japan, and Australia. Effective tools for institutional and regulatory control, certification, auditing, and professional training that ensure the sustainability and competitiveness of tourism services are revealed. The current state of the quality management system in the tourism sector of Ukraine is analysed: the current regulatory framework, in particular the Law of Ukraine ‘On Tourism’, DSTU EN 13809:2016, DSTU ISO 9001:2015, is characterised, and its partial adaptation to international requirements is identified. The key barriers to integration have been identified: fragmented regulation, limited participation of industry players in voluntary certification systems, and the absence of a national system for assessing the quality of tourism products. Relevant tools that can be implemented in Ukraine, taking into account the local conditions of tourism enterprises, have been identified: public-private partnership models, regional quality programmes (as in France and Canada), the introduction of eco-labels (as in Sweden and Germany), and the development of staff competencies based on standardised professional profiles. As a result of the study, an analytical typology of quality assurance models adapted to Ukrainian realities was proposed, and their comparative characteristics were visualised. The article is of scientific and practical value for specialists in the field of tourism, government agencies and the academic community interested in the implementation of innovative quality management practices at the national level.
Quality management mechanisms in tourism: transfer of international experience to ukrainian realities
Keywords: управління якістю в туризмі; концепція TQM (Total Quality Management); моделі оці нювання якості; модель SERVQUAL; European Foundation for Quality Management (EFQM); підходи GSTC (Global Sustainable Tourism Council); система сертифікації якості; стандарти ISO; quality management in tourism; TQM (Total Quality Management) concept; quality assessment models; SERVQUAL model; GSTC (Global Sustainable Tourism Council) approaches; quality certification system; ISO standards